Parametric Study Of Low Velocity Impact Using Finite Element Analysis - Mohd Sahri, Mohd Ridhuan; Che Muhamad, Che Muhamad Khairul Iezuadi; Abd. Latif, Mohd Juzaila; Mahmud, Jamaluddin (Trans Tech Publications, 2013)
An aircraft structural and material response is very complex when subjected to impact. It involves both elastic and plastic deformation in instant. Nevertheless, investigating this phenomenon is challenging yet interesting. Therefore, this research attempts to investigate the effect of selected parameters variation (i.e. material type, skin thickness and impact velocity) to the resulting equivalent plastic shear strain using finite element analysis (FEA). The finite element (FE) models were developed using commercially modeling and FE software to replicate an aircraft fuselage (target) and projectile according to the experimental setup and data established by other researcher [1]. The current study only focuses on the materials response and deformation behavior due low velocity (30 – 150 m/s) impact of a blunt object to a square shape target made of Al 2024T3 and aluminum alloy 7475 (AA 7475). In all cases (parameters variation), the resulting equivalent plastic strain has been determined and compared to the established data. It is found that the currents results are very close to the actual material response measured in experiments. This proves that simulated results are validated and the study contributed some knowledge to understanding the behaviour of the structural and material response in a low impact velocity. By varying selected parameters, the impact resistivity of the structure could be improved.